ภาพลักษณ์ของวิชาชีพพยาบาลในสื่อละครโทรทัศน์ไทย - ภู่ไพบูลย์ รุจา; ฟองแก้ว กังวาฬ (Journal of Thailand Nursing and Midwifery Council, 2017)
Objective: To examine the images of the nursing profession as portrayed in Thai television drama series. Design: Qualitative research. Methodology: This study examined a sample of 17 drama series broadcast on Thai free television channels 3, 5, 7, 9 and Thai PBS from 2005 to 2015. Out of a total of 931, the 17 television drama series were chosen by means of purposive sampling, based on the condition that they featured characters in the nursing profession. The data were analysed using content analysis, based on Stuart Hall’s theory of representation in the media. Results: The images of nurses in the selected drama series could be divided into 6 major groups. The positive images depicted nurses as committing themselves to their professional ideology, providing patients with protection and possessing ideal characteristics beftting well-bred ladies. The negative images showed nurses as servants, sex objects and portrayers of negative female attributes. Recommendations: This study showed Thai TV drama producers’ portrayal of the nursing profession was based on stereotypical ideas. Such portrayal was far from accurate, failing to take into consideration the intricate and diverse dimensions of the profession. The fndings of this study could help drama producers realise the negative impact that such inaccurate images might have on the nursing profession and any organisations associated with the nursing profession. Also, this study’s fndings could be used for planning proactive approaches to seeking the media’s cooperation in presenting positive and accurate images of the nursing profession.